Answer:
x=1 1/4 (1.25), y=1/4
Step-by-step explanation:
Since the equation "y=x-1" seems simple enough, we're going to plug that in for our other equation, "-4x+3=-2".
1. Rearrange y=x-1 to fit our other equation, -4x+3=-2.
y=x-1 (add 1 to both sides)
y+1=x x=y+1
2. Plug our newly rearranged equation into -4x+3=-2.
-4(y+1)+3=-2
-4y-4+3=-2 (distributive property)
3. Add/subtract like terms.
-4y-1=-2
4. Get y to be by itself.
-4y=-1 (add 1 to both sides)
y=1/4
1. Now for y=x-1. Plug 1/4 into y.
1/4=x-1
1 1/4=x